PEMBUATAN MINUMAN PROBIOTIK BERBASIS KULIT NANAS (Ananas comosus (L.) Merr.) MENGGUNAKAN Lactobacillus casei subsp. casei R-68 YANG DIISOLASI DARI DADIH - Elsaputra '; Usman Pato; Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Probiotic drink is a beverage produced from the lactic acid fermentation by lactic acid bacteria. Probiotic drink can be made from the extract of pineapple skin, hereinafter referred to as probiotic drinks pineapple skin juice. The purpose of this study was to obtain the optimal addition of sucrose (S) in the manufacture of probiotic drink pineapple skin juice (K) that meet quality standards and preferred by consumers. This study was conducted experimentally using Completely Randomized Design (CRD) with four treatments (S1K1 = without sucrose, S2K2 = 5% sucrose, S3K3 = 8.5% sucrose and S4K4 = 12% sucrose). Each treatment was repeated four times to obtain 16 units of trial. Data were analyzed statistically using Analysis of Variance (ANOVA), if F count ≥ F table then continued with test of Duncan's New Multiple Range Test (DNMRT) at 5%. The results show that the variation of sucrose added significantly affected the total lactic acid bacteria, total solids, taste and overall acceptance test, but did not influence the pH value, colour and aroma of fermented drink. The best treatment was obtained on the addition of sucrose 12% with a lactic acid bacteria total of 7.08 cfu/ml, a solid total of 12.67% with a pH value of 3.94 as well as preferred by the panelists (consumers). Keywords: Probiotic, pineapple skin juice, Lactobacillus casei subsp. casei R-68 and dadih.